Field Tests and Numerical Modeling of Vehicle Impacts on a Boulder Embedded in Compacted Fill. Issue 4 (December 2014) - Reese, Lynsey; Qiu, Tong; Linzell, Daniel; O'Hare, Edward; Rado, Zoltan
Landscape Vehicular Anti-Ram (LVAR) systems are a group of protective barriers, which are designed using natural materials (e.g., boulders) and have proven to both effectively protect sensitive structures against threats and be aesthetically pleasing. This paper presents two consecutive vehicular crash tests hitting the same single boulder embedded in AASHTO coarse aggregate fill. A LS-DYNA model was developed to simulate the field-scale tests, which were instrumented with high-speed cameras and pressure cells. A readily available truck model from the National Crash Analysis Center was modified and implemented in the LS-DYNA model. The boulder and surrounding soil were modeled using the Mohr-Coulomb failure criteria. The model parameters were calibrated using results from the first field-scale test with a truck traveling at 48.3 km/hr (30 mph) impacting the LVAR system. The calibrated model was then used to simulate the second field-scale test, which involved a truck traveling at 80.5 km/hr (50 mph) impacting the same LVAR system without resetting the boulder or soil. The calibrated model was able to provide the global response of the system, including the time-history of the translational displacement and rotation of the boulder, and was in good agreement with field-scale test results. This suggests that the overall global response was dominated by the dynamic behavior of the truck and boulder system upon impact. Hence, a simple material model for soil and boulder is sufficient for simulating the tests conducted.